New Insights on Juvenile Psoriatic Arthritis - Brunello, Francesco; Tirelli, Francesca; Pegoraro, Luca; Dell'Apa, Filippo; Alfisi, Alessandra; Calzamatta, Giulia; Folisi, Camilla; Zulian, Francesco (Frontiers in Pediatrics, 2022)
Juvenile psoriatic arthritis (JPsA) is a relatively rare condition in childhood as it represents approximately 5% of the whole Juvenile Idiopathic Arthritis (JIA) population. According to International League of Associations of Rheumatology (ILAR) classification, JPsA is defined by the association of arthritis and psoriasis or, in the absence of typical psoriatic lesions, with at least two of the following: dactylitis, nail pitting, onycholysis or family history of psoriasis in a first-degree relative. However, recent studies have shown that this classification system could conceal more homogeneous subgroups of patients differing by age of onset, clinical characteristics and prognosis. Little is known about genetic factors and pathogenetic mechanisms which distinguish JPsA from other JIA subtypes or from isolated psoriasis without joint involvement, especially in the pediatric population. Specific clinical trials testing the efficacy of biological agents are lacking for JPsA, while in recent years novel therapeutic agents are emerging in adults. In this review, we summarize the clinical features and the current evidence on pathogenesis and therapeutic options for JPsA in order to provide a comprehensive overview on the clinical management of this complex and overlapping entity in childhood.